Optimization Using Central Composite Design and The Desirability Function For W/O Transparent Cosmetic Hair Wax (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The objective of this study was to design and optimize a w/o transparent cosmetic hair wax by using central composite design and desirability function. Preliminary trial was conducted for screening the fixative agent and emulsifier. From a Preliminary trial study acryset FS and ceteareth 20 was taken as fixative agent and emulsifier respectively. The prepared hair wax was evaluated for phase separation, homogeneity, grittiness, pH, transparency, viscosity, curl retention, flaking test, humidity resistance of treated hair tresses and stability study. A central composite design was employed to study the effect of acryset FS (X1) and ceteareth 20 (X2) on transparency (Y1), viscosity (Y2) and curl retention (Y3). In this present study, the following constraints were arbitrarily used for the selection of an optimized batch: transparency > 90%, viscosity=1,25,000 to 1,50,000 cps and curl retention = 81% to 86%. Multiple linear regression analysis, ANOVA, graphical representation of the influence factor by 3D plots and desirability plot were performed by using design expert 12. To validate the evolved mathematical models, a check point was selected from its desirability value 1. The results of ANOVA suggested that calculated F values calculated of all dependent variables are greater than tabulated values. Prepared checkpoint batch evaluated values were found to be similar with the predicted values and it found to be stable in stability study. Unique hair styling transparent hair wax delivers the high humidity resistance, excellent curl retention and no flakes and it meets today's market trend.